Supporting Universal Prevention Programs: A Two-Phased Coaching Model - Becker, Kimberly D. (2013)
Schools are adopting evidence-based programs designed to enhance students’ emotional and behavioral competencies at increasing rates (Hemmeter, Snyder, & Artman, 2011). At the same time, teachers express the need for increased support surrounding implementation of these evidence-based programs (Carter & Van Norman, 2010). Ongoing professional development in the form of coaching may enhance teacher skills and implementation (Noell et al., 2005; Stormont, Reinke, Newcomer, Darney, & Lewis, 2012). There exists a need for a coaching model that can be applied to a variety of teacher skill levels and one that guides coach decision-making about how best to support teachers. This article provides a detailed account of a two-phased coaching model with empirical support developed and tested with coaches and teachers in urban schools (Becker, Bradshaw, Domitrovich, & Ialongo, 2013). In the initial universal coaching phase, all teachers receive the same coaching elements regardless of their skill level. Then, in the tailored coaching phase, coaching varies according to the strengths and needs of each teacher. Specifically, more intensive coaching strategies are used only with teachers who need additional coaching supports whereas other teachers receive just enough support to consolidate and maintain their strong implementation. Examples of how coaches used the two-phased coaching model when working with teachers who were implementing two universal prevention programs (i.e., the PATHS(®) curriculum and PAX Good Behavior Game [PAX GBG]) provide illustrations of the application of this model. The potential reach of this coaching model extends to other school-based programs as well as other settings in which coaches partner with interventionists to implement evidence-based programs.